Tradisi Mendirikan Rumah Di Kampung Adat Kuta, Kabupaten Ciamis - Ranti Furiya Adisti (CV. Aksara Global, 2024)
In this era of globalization, many people do not want to be left behind in one of the developments in sophistication is that many people want to make comportable and more modern residential duildings in accordance wuth developments epoch, both in terms of building materials, as well as other equipment. In contrast to the people of Kuta Traditional Village in Ciamis Regency who continue to maintain its traditions, customs, and culture are still strong in people’s belief in their ancestors and clinging to the beliefs that are considered as the mandate of the ancestors. This study aims to find out how the traditional of building a house in Kuta Traditional Village knowing the rules in establishing a house in Kuta Traditional Village, as well as to find out why the traditional of building a house in Kuta Traditional Village is still carried out in the modernization era. This research is descriptive with qualitative methods, data collection is carried but by observation, interviews, literature studies and documentation. The results showed that until now the tradition of building a house in Kuta Traditional Village is still carried out by following the rules, rituals or existing traditions